2021
DOI: 10.3390/jcm10184204
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response after BNT162b2 Vaccination in Healthcare Workers Previously Exposed and Not Exposed to SARS-CoV-2

Abstract: The Pfizer/BioNtech Comirnaty vaccine (BNT162b2 mRNA COVID-19) against SARS-CoV-2 is currently in use in Italy. Antibodies to evaluate SARS-CoV-2 infection prior to administration are not routinely tested; therefore, two doses may be administered to asymptomatic previously exposed subjects. The aim of this study is to assess if any difference in antibody concentration between subjects exposed and not exposed to SARS-CoV-2 prior to BNT162b2 was present after the first dose and after the second dose of vaccine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
3
0
0
1
Order By: Relevance
“…Considering the impact of previous infection with SARS-CoV-2 on serological response, as previously reported [ 5 , 19 , 27 , 28 , 29 , 30 , 31 , 32 ], we confirmed that this was associated with significantly higher antibody levels, with approximately half of the subjects displaying values exceeding the upper limit of detection and a remaining 20% in the immediately lower quintile. This finding is relevant, considering that our study was performed at 4–5 months post-vaccination, whereas most studies evaluated individuals at 3 to 7 weeks post-vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Considering the impact of previous infection with SARS-CoV-2 on serological response, as previously reported [ 5 , 19 , 27 , 28 , 29 , 30 , 31 , 32 ], we confirmed that this was associated with significantly higher antibody levels, with approximately half of the subjects displaying values exceeding the upper limit of detection and a remaining 20% in the immediately lower quintile. This finding is relevant, considering that our study was performed at 4–5 months post-vaccination, whereas most studies evaluated individuals at 3 to 7 weeks post-vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is concordant with previous reports that indicated the seroconversion rate was highest at 21 days after the first dose of the BNT162b2 mRNA vaccine [13,14]. However, the anti-S antibody level in our patient displayed a tendency to be lower than the median value of antibodies concentration found in infection-naïve individuals on day 21 post-vaccination [13,15]. Although the involvement of PS in the development of host humoral immune response remains unclear, previous studies have shown that PS signaling through TAM receptor (MERTK) on lymphocyte T cells plays a role in inducing proliferation, cytokines release, and differentiation into memory cells [16,17].…”
Section: Discussionsupporting
confidence: 92%
“…Although this more intense response in the production of antibodies has been previously reported by (14,15,18,19), it is clear that there may be more differences in the immune response mounted by individuals with natural infection and without previous natural disease, and some of them could even help to explain the disparity in the humoral response. We evaluated a panel of cytokines and cell populations in peripheral blood and the follow-up to identify these differences.…”
Section: Discussionsupporting
confidence: 54%